Ammonia concentration monitoring using Arduino platform - Petric, Marko; Dodigović, Filip; Grčić, Ivana; Mrakužić, Petar; Radetić, Lucija; Topić, Mateo (2019)
In order to evaluate the efficacy of ammonia photocatalysis, it is necessary to continuously monitor its concentration during the process. This paper presents ammonia concentration monitoring using a low cost (non-professional) electronic device. The device is based on an open source electronic platform, and it is composed of the MQ-137 ammonia detection sensor, connected to the Croduino Basic 2 board. Sensitive material of the sensor is a metal oxide (SnO2). The change in the ammonia concentration causes a change in the electrical resistance, which is measured and used for the ammonia concentration estimation. Four measurements, with ammonia concentration ranging from 0-500 ppm were performed in the controlled environment. With the purpose of the device calibration and repeatability test, along with a low-cost device, the monitoring was carried out also with a professional device, Geotech GA5000 gas analyser. Using the information provided in the sensor datasheet, together with the measured data, the measurement error of the low-cost device was assessed. After calibration, ammonia concentrations measured using a low-cost device, are consistent with those obtained from the professional device.
Bibliografija: 15 jed.
Summary.
Keywords: Arduino; Fotokatalizator -- Koncentracija amonijaka -- Fotokataliza amonijaka